Sign Meaning Index in Bumi Tere Liye’s Novel and Their Implication on Learning Material of Literature at SMK - B.Syukroni Baso; Johar Amir; Kembong Daeng (International Journal of Science and Applied Science: Conference Series, 2022)
The purpose of this study was to describe the meaning of the index sign in Tere Liye's earth novel. The novel was chosen to be the object of research because it uses a lot of sign systems in expressing ideas and ideas. The type of research is qualitative descriptive research because it describes or describes the data that researchers find in the novel of the earth with an inventory technique to find and collect a number of data, read-listen techniques to obtain information accurately, and record the data that has been collected. After that, the researcher analyzed to describe the meaning contained in the signs in the novel with several stages: (1) data analysis, (2) data classification, (3) data repetition, (4) data presentation. The results showed that there were signs, namely icon marks. There are 11 index data. The dominant data found by the researcher is icon image data. This proves that the icon data is used as a manifestation of the description of the actor seen from the nature and character that makes him the actor in the novel.